(untitled) (Research, Society and Development, 2026)
Introduction: The ethics of everyone can constitute a pedagogical tool that enhances human relationships, equipping graduates to deal with the diverse conflicts of daily work. Objective: To identify, from the perspective of undergraduate nursing students, the elements necessary for the development of ethical environments in the university. Method: A qualitative, descriptive, and exploratory research using the principles of Lev Vygotsky’s Historical-Cultural Theory as a theoretical framework. A total of 14 students from the fourth to the tenth semester participated. Data collection occurred in two stages: focus group technique and imagistic production from March to June 2022. The analysis was conducted using Karl Mannheim’s Documentary Method of Image Analysis, updated by Ralph Bohnsack. Dialogues were interpreted through textual discursive analysis. Results: Imagistic perceptions reveal the importance of actions in the university space, the role of teachers and the university in shaping environments, and the constructed perceptions and images of ethical environments enable an ethical exercise that strengthens higher education in nursing. Final considerations: It is expected to contribute to the improvement of curricula and pedagogical projects and to train educators and students for the development of ethical environments in undergraduate education.